2022
DOI: 10.3390/antiox11040611
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antioxidant Chinese Herbal Medicines: Links between Traditional Characters and the Skin Lipoperoxidation “Western” Model

Abstract: The relationship between lipid peroxidation and inflammation has been accepted as a paradigm in the field of topical inflammation. The underlying biochemical mechanisms may be summarised as unspecific oxidative damage followed by specific oxidative processes as the physio pathological response in skin tissues. In this experimental review we hypothesise that the characteristics attributed by Traditional Chinese Medicine (TCM) to herbal drugs can be linked to their biomolecular activities within the framework of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 141 publications
0
4
0
Order By: Relevance
“…Studies have shown that Lycium barbarum extract has a neuroprotective effect on radiation-induced neurobehavioral changes such as cognitive impairment and depression [ 62 ]. From the point of view of antioxidation, many TCMs may play a better role, such as Cistanche deserticola and Houttuynia cordata [ 63 , 64 ]. In the future, the long-term anti-radiation effect of TCM can be studied using this model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Lycium barbarum extract has a neuroprotective effect on radiation-induced neurobehavioral changes such as cognitive impairment and depression [ 62 ]. From the point of view of antioxidation, many TCMs may play a better role, such as Cistanche deserticola and Houttuynia cordata [ 63 , 64 ]. In the future, the long-term anti-radiation effect of TCM can be studied using this model.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reveal that using walnut shell WS is an excellent alternative and attractive material for removing carcinogenic compounds by adsorption due to affordability and high efficiency [10][11][12]. It can also be used as an antioxidant and antimicrobial compound, which has gained considerable attention in medical applications, especially, for treating inflamed skin, ulcers, and hyperhidrosis [13,14]. Producing adsorbents through the transformation of waste material has helped obtain the useful product for industrial and scientific research [4].…”
Section: Introductionmentioning
confidence: 99%
“…As an important component of traditional Chinese medicine, many Chinese herbal formulas with anti-inflammatory, antibacterial, immunomodulatory, and digestion-promoting functions have been developed [13][14][15][16][17][18]. For instance, traditional Chinese medicine theory suggests that Radix Astragali has anti-inflammatory effects [16], and four phenolic derivatives isolated from Radix Astragali exhibit potent inhibitory effects on tumor necrosis factor-α (TNF-α) production and TNF-α, cyclooxygenase-2 (COX-2), interleukin-1β (IL-1β), IL-6, and inducible nitric oxide synthase (iNOS) mRNA expression at 50 µM in lipopolysaccharide (LPS)-induced mouse peritoneal macrophages [19]. The essential oil from Artemisia argyi inhibits inflammation through the down-regulation of JAK/STAT signaling in LPS-induced RAW264.7 cells [20].…”
Section: Introductionmentioning
confidence: 99%